WOMEN AT THE LEVEL OF MANAGEMENT, AGENCY CONFLICT MECHANISMS, AND FINANCIAL PERFORMANCE - Surjaatmaja, Lukas; Wijaya, Hendra (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
This study analyzes the effect of female representation in top management, agency conflict mechanism on firm performance in Indonesia Manufacturing Firms. Agency conflict in this reseach consist of managerial ownership, institutional ownership, and debt. The sample of this study consist of 90 manufacturing firms over the period 2013-2017. This study measures firm performance with return on asset and return on equity. Data on this research were analyzed using multiple regression. This study found that female representation in top management and managerial ownership do not affect firm performance. This study also found that institutional ownership positively affects the firm performance and debt negatively affects the firm performance